Sosialisasi Pemanfaatan Tanaman Toga dalam Meningkatkan Pendapatan Ibu-Ibu TP PKK Desa Lenteng Timur - Jannatul Firdaus; Hertin Khalifatun Nisa Arifah; Edi Awan; Nurul Hidayat (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Herbal medicine is one type of traditional Indonesian medicine made from natural ingredients and is a cultural heritage passed down from generation to generation. One of the problems is the lack of knowledge about the benefits of TOGA plants, which are not only used as kitchen spices but can also be utilized as powdered herbal drinks. The main objective of this community service activity is to train and disseminate information on the education and production of powdered herbal drinks that can be sold to the PKK women in Lenteng Timur village, providing additional income for their families. The aim of this research is to determine whether TOGA plants can help the PKK women in Lenteng Timur village earn more income. The methods of socialization, education, training, and evaluation are used in this study. The findings show that before the training, 77.5% of the PKK women in Lenteng Timur village only knew about the use of TOGA plants as powdered herbal drinks; however, after the training, their knowledge increased by 22.5%.